2016
DOI: 10.1017/s0954579416000705
|View full text |Cite
|
Sign up to set email alerts
|

Development of self-inflicted injury: Comorbidities and continuities with borderline and antisocial personality traits

Abstract: Self-inflicted injury (SII) is a continuum of intentionally self-destructive behaviors, including nonsuicidal self-injuries, suicide attempts, and death by suicide. These behaviors are among the most pressing yet perplexing clinical problems, affecting males and females of every race, ethnicity, culture, socioeconomic status, and nearly every age. The complexity of these behaviors has spurred an immense literature documenting risk and vulnerability factors ranging from individual to societal levels of analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 216 publications
1
15
0
1
Order By: Relevance
“…NSSI has a higher prevalence among adolescents and young adults, and is associated with an array of psychosocial issues and is believed to be a transdiagnostic manifestation arising from an underlying vulnerability inherent to the psychopathology (Crowell et al, 2009; Selby et al, 2015). NSSI differs from suicide in that it is not associated with suicidal inclinations: furthermore, the strategies implemented for behaviors aiming at regulating negative emotions are different from those used to manage behaviors aiming at causing death (Crowell and Kaufman, 2016). Unlike suicide, NSSI has an immediate and short-term impact, and must be carried out repeatedly to produce the desired outcome (Shaffer and Jacobson, 2009).…”
Section: Non-suicidal Self-injury and Suicidementioning
confidence: 99%
“…NSSI has a higher prevalence among adolescents and young adults, and is associated with an array of psychosocial issues and is believed to be a transdiagnostic manifestation arising from an underlying vulnerability inherent to the psychopathology (Crowell et al, 2009; Selby et al, 2015). NSSI differs from suicide in that it is not associated with suicidal inclinations: furthermore, the strategies implemented for behaviors aiming at regulating negative emotions are different from those used to manage behaviors aiming at causing death (Crowell and Kaufman, 2016). Unlike suicide, NSSI has an immediate and short-term impact, and must be carried out repeatedly to produce the desired outcome (Shaffer and Jacobson, 2009).…”
Section: Non-suicidal Self-injury and Suicidementioning
confidence: 99%
“…One of the major challenges in diagnosing, treating and studying BPD is the typically high levels of comorbid disorders [ 5 ], including anxiety [ 9 , 10 ], depression and other mood disorders [ 10 13 ], substance use disorders [ 2 , 4 , 14 , 15 ], suicidal and parasuicidal behaviour [ 13 , 16 ] and Antisocial Personality Disorder (ASPD) [ 5 , 17 19 ]. High levels of comorbidity not only make it difficult to diagnose and to treat BPD, but also to disentangle correlates and antecedents of BPD from those of comorbid disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of stress exposure on an expectant mother can have an early and enduring impact on her child’s functioning (Sandman et al, 2011 ). Exposure to prenatal stress has been associated with increased fearful behavior (Bergman et al, 2007 , 2008 ; Davis et al, 2007 ; Werner et al, 2007 ) and stress reactivity (Yehuda et al, 2005 ; Oberlander et al, 2008 ; Davis et al, 2011 ), placing these children at risk for developing internalizing symptoms later in life ( Crowell and Kaufman, in press ). For instance, longitudinal work from Davis and Sandman ( 2012 ) showed that children exposed to maternal anxiety and stress in utero exhibit more internalizing symptoms across childhood, with rank order stability persisting into adolescence (O’Donnell et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%